The Heterogeneous Economic Consequences of Works Council Relations - Pfeifer, Christian (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
I use a question about works council relations from the 2006 wave of the IAB Establishment panel to analyze the heterogeneous effects of works councils on productivity, wages, and profits. The results indicate that the effects differ significantly between works council relationship types in a systematic pattern. The overall findings are in line with productivity-enhancing and rent-sharing functions of works councils.
Keywords: Codetermination; Firm Performance; Industrial Relations; Works council; 330 Wirtschaft